2019
DOI: 10.3390/s19235086
|View full text |Cite
|
Sign up to set email alerts
|

Water Pipeline Leakage Detection Based on Machine Learning and Wireless Sensor Networks

Abstract: The detection of water pipeline leakage is important to ensure that water supply networks can operate safely and conserve water resources. To address the lack of intelligent and the low efficiency of conventional leakage detection methods, this paper designs a leakage detection method based on machine learning and wireless sensor networks (WSNs). The system employs wireless sensors installed on pipelines to collect data and utilizes the 4G network to perform remote data transmission. A leakage triggered networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 49 publications
0
44
0
1
Order By: Relevance
“…As examples of use of such models, [1] presents a stochastic model for failure forecasting of water mains using the collected data, and [2] provides various intelligent approaches for the prediction. Also, [32] presents a WSNbased monitoring scheme based on a leak identification method for water pipelines that relies on the combined use of Principal Components Analysis (PCA) and SVM. The highest identification accuracy achieved by this model was around 98%.…”
Section: Related Workmentioning
confidence: 99%
“…As examples of use of such models, [1] presents a stochastic model for failure forecasting of water mains using the collected data, and [2] provides various intelligent approaches for the prediction. Also, [32] presents a WSNbased monitoring scheme based on a leak identification method for water pipelines that relies on the combined use of Principal Components Analysis (PCA) and SVM. The highest identification accuracy achieved by this model was around 98%.…”
Section: Related Workmentioning
confidence: 99%
“…Regardless of the technique used, the amount of data generated by water distribution monitoring systems is large. As an example, experiments conducted by Liu et al showed that 100 datasets of size 5000 samples can be generated in 1200s [8]. This is equivalent to 1.5 million samples/hour for a monitoring network consisting of around 600 nodes [8].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, experiments conducted by Liu et al showed that 100 datasets of size 5000 samples can be generated in 1200s [8]. This is equivalent to 1.5 million samples/hour for a monitoring network consisting of around 600 nodes [8]. To address this issue, multiple potential solutions can be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-sensor data fusion combines redundant data from multiple low-cost sensors to achieve a more accurate information whose quality exceeds that achieved by using a single sensor [ 36 , 38 ]. In addition, the low-power consumption requirement and the need for a WWPM to go unattended for a long period of time without any replacement of the sensor node’s battery [ 33 , 39 , 40 ], affects the choice of multi-sensor data fusion technique that can be used. Multi-sensor data fusion in WSN can either be done via a centralized, decentralized or in a distributed manner [ 37 , 41 ].…”
Section: Introductionmentioning
confidence: 99%